An improved operational framework for defects liability management system in design and build public hospital projects / Haryati Mohd Isa - Mohd Isa, Haryati (Institute of Graduate Studies, UiTM, 2014)
Contrary to the belief that the Design and Build (DB) procurement approach will result in better project outcomes, many DB projects, particularly public buildings are short of meeting the expectations. One of the major issues faced is the construction defects. Clients usually are at loss while trying to configure how this matter should be dealt with. Consequently, they normally end up rectifying most of the defects at their own cost. In appreciating the need to resolve this continuing problem, the government has introduced a Defects Liability Management (DLM) System by appointing a Service Provider (SP) to record and manage the defects identified during the Defects Liability Period (DLP). Realising the opportunity that can be learnt from this system in providing insights to improve the implementation of future projects, this research was mooted. The aim of this study is to develop an operational framework for improving the current DLM system practiced in DB public hospitals in Malaysia. Seven public hospitals are chosen as the case study. A mixed method approach was adopted for the research.